2018
DOI: 10.1186/s12889-018-5912-9
|View full text |Cite
|
Sign up to set email alerts
|

Pain and self-rated health among middle-aged and older Canadians: an analysis of the Canadian community health survey―healthy aging

Abstract: BackgroundPain is an important health problem adversely affecting functionality and quality of life. Though self- rated health (SRH) is a major predictor of mortality, its relationship with pain is not well understood. We explore 1) how pain and age interact to influence SRH, and 2) provincial variations in SRH across Canada.MethodsWe analyzed cross-sectional data from Statistics Canada’s Canadian Community Health Survey-Healthy Aging (n = 30,685), which targeted those 45 years and older and was conducted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
3
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 39 publications
6
14
3
8
Order By: Relevance
“…No independent associations between SRH and living conditions such as educational level, country of birth, living alone, cash margin and social support were found, even though low educational level and lack of social support were associated with poorer than good SRH in the bivariate analyses. This contradicts the findings from some previous studies where for example education [20,36], wealth and ethnicity [27] as well as social support [19] and loneliness [33] have been found to be associated with SRH in the elderly. However, some of these findings were obtained among younger elderly, whereas a smaller study on very old people, 80-89 years of age, in Sweden and Latvia did not find any association between SRH and educational level, income, marital status or social support [23] and one study in Spain found that the effect of social class among those aged 65 or older decreased with age [9].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…No independent associations between SRH and living conditions such as educational level, country of birth, living alone, cash margin and social support were found, even though low educational level and lack of social support were associated with poorer than good SRH in the bivariate analyses. This contradicts the findings from some previous studies where for example education [20,36], wealth and ethnicity [27] as well as social support [19] and loneliness [33] have been found to be associated with SRH in the elderly. However, some of these findings were obtained among younger elderly, whereas a smaller study on very old people, 80-89 years of age, in Sweden and Latvia did not find any association between SRH and educational level, income, marital status or social support [23] and one study in Spain found that the effect of social class among those aged 65 or older decreased with age [9].…”
Section: Discussioncontrasting
confidence: 99%
“…We did not find any associations between other lifestyle factors than physical activity and SRH even though previous studies have found an association between e.g. smoking and SRH in the elderly [18,19,33]. The lack of association with smoking is possibly related to the small number of smokers (2%) in our study.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Self-rated health is considered a measure of general health status and is often used as a predictive measure of health outcomes [9,10]. Several socio-economic factors (SES) such as educational level [11], cohabitation, income level [4,11,12], and place of residency affect SRH in older people [13].…”
Section: Introductionmentioning
confidence: 99%